Reliability and durability problems of load bearing concrete structures for electric power transmission lines/Elektros tinklo laikančiųjų gelžbetoninių konstrukcijų patikimumo ir ilgalaikiškumo problemos - Vadlūga, Romualdas; Kliukas, Romualdas (Journal of Civil Engineering and Management, 2000)
Experimental and theoretical investigations associated with reliability and durability problems of concrete structures of electric power and communication systems have been carried out by scientists of Vilnius Gediminas Technical University since 1959. An attempt to generalise the accumulated statistical data enabling to evaluate reliability and durability of such structures is presented in this article. It has been determined that concrete pylons of supports of electric power overhead lines under long-term service (over 30 years) are with defects and damages, and the most characteristic of these are vertical cracks close to the longitudinal reinforcing bars, delaminated or fallen down concrete protective cover, naked longitudinal reinforcement which is corroded along 0,5-2 m intervals (not along the whole its length). Cross-sectional area of corroded reinforcement is reduced not substantially, because corrosion becomes slower due to ventilation after opening of a wide crack. Technical state of spun concrete pylons of annular cross-section is better and they are more reliable and durable in comparison with vibrated concrete pylons duringr the same time in service. Reliability and durability of concrete pylons of supports of electric power network are governed by structural solution, condition of manufacture, erection and operation. Durability of concrete pylons can be achieved by using concrete of sufficient density and resistance to aggressive environmental actions. Durability of pylons is very much dependant on concrete structure. Concrete density increases with decrease of v/c ratio. Quality of concrete depends on its mix compaction and hardening conditions. Concrete hardening process should be as mild as possible. Additional effects causing microfracture of concrete should not appear during manufacture, transportation and erection of pylons. Prestressing of concrete during manufacture should be mild-gradual. Durability of pylons is highly influenced by quality of concrete protective cover. The latter should be of adequate thickness. Since it has been established that the cover thickness is not always adequate, sometimes deviations from values specified in design are observed, it was proposed to manufacture pylons with thicker protective concrete cover. Production of vibrated concrete pylons of rectangular cross-section according to new type developed drawings has started in Kaunas factory of concrete pylons. Provision of transverse reinforcement along the whole pylon length is proposed for increasing torsional strength. It is worth discussing whether it is expedient to start again manufacturing more reliable and durable spun concrete pylons of annular cross-section. Full scale tests of concrete pylons in natural conditions indicated that strength to bending about the axis perpendicular to transmission line is sufficient even of pylons in service for 25–30 years. But these pylons are not sufficiently strong to bending in other direction and especially when they are subjected to bending with torsion. Reliability and durability of concrete vibrated pylons are also governed by structural solution, technology of manufacture and conditions of erection and service.Article in Lithuanian.First Published Online: 26 Jul 2012